COGNITIVE BEHAVIORAL THERAPY: AN OPTION FOR CHANGING INTERNAL PICTURE OF DISEASE IN PATIENTS WITH CORONARY ARTERY DISEASE - ANTON V. Solodukhin; ANDREY V. Seryi; MIKHAIL S. Yanitskiy; OLGA A. Trubnikova (Фундаментальная и клиническая медицина, 2017)
Here we review the data on internal picture of the disease (IPD) phenomenon and its features in patients with coronary artery disease (CAD). We describe the recent classification of IPD and the data of latest experimental studies. We then analyze the interrelations between IPD, psychosocial and behavioral status. In particular, non-adaptive IPD may occur under the cardiogenic life-threatening conditions. Furthermore, we suggest cognitive behavioral therapy as a promising option for the treatment of IPD, with a detailed description of specific techniques.